Fixed Point Theorems for α,k,θ,φ-Contraction Multivalued Mappings in b-Metric Space - Youssef Errai; El Miloudi Marhrani; Mohamed Aamri (Abstract and Applied Analysis)
We present the concept of α,k,θ,φ-contractive multivalued mappings in b-metric spaces and prove some fixed point results for these mappings in this study. Our results expand and refine some of the literature’s findings in fixed point theory.